Electronic collaboration toward social health outcomes - Biswas, Rakesh; Maniam, Jayanthy *; Lee, Edwin Wen Huo; Umakanth, Shashikiran; Das, Premalatha Gopal (IGI Global, 2009)
This is an illustrative process description of a collaborative project utilizing a multidisciplinary approach. The requirement for collaboration originated in an attempt to optimally answer the needs of individual patients and health professionals for information to allow them to achieve better health outcomes. This chapter introduces the problem statement through the auto-ethnographic reflections of three project developers. These reflections illustrate individual experiential agendas that initiated electronic collaboration among diverse stakeholders in the health care network. Each reflection also illustrates the sequence of events in a collaborative process beginning at the individual level and growing through the interaction of multiple individuals including patients, their relatives, health professionals, and other actors in the care giving network. This chapter describes how collaboration was sustained and further developed into an operational model.